Nursing Interventions to Improve Quality of Life in Palliative Cancer Care Patients: A Scoping Review - Agung Subakti Nuzulullail; Halfie Zaqiyah Gusti Puspitasari; Dwina Oktavia Deli; Dana Prayoga Irawan (Universitas Airlangga, 2026)
Introduction: In the last few decades, Quality of Life (QoL) in palliative cancer patients has become an important aspect to consider. Nurses play a crucial role in improving QoL through nursing interventions. However, reviews on the variety of nursing interventions to improve QoL in palliative cancer patients have not been widely conducted. This scoping review aims to identify findings related to nursing interventions and palliative care outcomes for cancer with cancer. Method: The scoping review was conducted through PubMed, ScienceDirect, ProQuest, and EBSCOhost. The Arksey and O’Malley framework was used to address the research question: “What nursing interventions are implemented to improve the QoL of palliative care cancer patients?” Study selection is based on the PRISMA-ScR 2020 guidelines with the scheme P: palliative cancer patients, I: nursing interventions, C: no intervention, and O: improvement in quality of life. The inclusion criteria were original articles published between 2020 and 2025, Randomized Controlled Trials (RCTs), quasi-experimental, and cohort studies. Review articles, protocols, commentaries, and books were excluded. Quality assessment was conducted using the JBI Critical Appraisal tool Results: From 990 records, 8 articles met the criteria. Nursing interventions included education, emotional and spiritual support, mediation, decision-making, nursing planning, nutritional support, comfort care, complementary therapy, and community service coordination. Improvements in QoL were observed in symptom reduction, social support, psychological, information, patient independence, and care satisfaction. Conclusions: Nursing interventions are crucial for improving the QoL of palliative cancer patients. Future research should test nursing interventions in palliative cancer patients, considering culture, special groups, and community services.